Supported housing programs for persons with serious mental illness in rural northern communities: A mixed method evaluation - Bailey Patricia H; Rose Don; Duncan Craig; Forchuk Cheryl; Montgomery Phyllis; Veluri Ramamohan (BMC, 2008)
Abstract Background During the past two decades, consumers, providers and policy makers have recognized the role of supported housing intervention for persons diagnosed with serious mental illness (SMI) to be able to live independently in the community. Much of supported housing research to date, however, has been conducted in large urban centers rather than northern and rural communities. Northern conditional and contextual issues such as rural poverty, lack of accessible mental health services, small or non-existing housing markets, lack of a continuum of support or housing services, and in some communities, a poor quality of housing challenge the viability of effective supported housing services. The current research proposal aims to describe and evaluate the processes and outcomes of supported housing programs for persons living with SMI in northern and rural communities from the perspective of clients, their families, and community providers. Methods This research will use a mixed method design guided by participatory action research. The study will be conducted over two years, in four stages. Stage I will involve setting up the research in each of the four northern sites. In Stage II a descriptive cross-sectional survey will be used to obtain information about the three client outcomes: housing history, quality of life and housing preference. In Stage III two participatory action strategies, focus groups and photo-voice, will be used to explore perceptions of supported housing services. In the last stage findings from the study will be re-presented to the participants, as well as other key community individuals in order to translate them into policy. Conclusion Supported housing intervention is a core feature of mental health care, and it requires evaluation. The lack of research in northern and rural SMI populations heightens the relevance of research findings for health service planning. The inclusion of multiple stakeholder groups, using a variety of data collection approaches, contributes to a comprehensive, systems-level examination of supported housing in smaller communities. It is anticipated that the study's findings will not only have utility across Ontario, but also Canada.